The anthropological pessimism in Hobbes from a Polian perspective - Aparicio Aldana, Zhenia Djanira (Mercurio Peruano, 2018)
The philosophy of Hobbes is oriented in a special way to justify the existence of the State under an absolutist system. For this author, the State is presented as an artificial person who provides security and peace, to a man involved in a state of nature of hatred and war. The anthropological pessimism of modern man, is currently reflected in a reductionism, typical of the crisis of contemporary culture, which is demonstrated in the loss of meaning. For Leonardo Polo, the problem arises when the answer to the attempt to discover what that vital force is, focuses on a single aspect or as Polo says "in only one stripe of that force"; it is at this moment when reductionism is taken into account.